Coexistent squamous cell carcinoma of lung with Aspergillosis diagnosed by cytology - Leelamma, Jayalakshmy Payippat; Mohammed, Babitha Alingal; K., Subitha (International Journal of Advances in Medicine, 2017)
Aspergillus infestation in squamous cell carcinoma (SCC) of lung has been reported in pathology specimens but not on fine needle aspiration cytology (FNAC) smears. We report a case of concurrent Aspergillosis and SCC of lung diagnosed by cytology in a 72 year old man who presented with cough and breathlessness. Computerized tomography (CT) thorax revealed right lower lobe consolidation with ill-defined nodular opacities and central cavitation. CT guided aspiration smears from the lung lesion revealed malignant squamous cells dispersed in single and occasional groups suggesting SCC. Cytological smears and cell block study of the fluid aspirated from the cavity showed fungal hyphae, malignant squamous cells and necrotic debris and thus a diagnosis of SCC with Aspergillus colonization was established. To our knowledge, there has not been any reported case of coexistent pulmonary SCC and fungus proven by cytology in literature.